Current Status of Phage Therapy against Infectious Diseases and Potential Application beyond Infectious Diseases - Hao-Ming Xu; Wen-Min Xu; Long Zhang (International Journal of Clinical Practice)
Intestinal microbiota plays a key role in regulating the pathogenesis of human disease and maintaining health. Many diseases, mainly induced by bacteria, are on the rise due to the emergence of antibiotic-resistant strains. Intestinal microorganisms include organisms such as bacteria, viruses, and fungi. They play an important role in maintaining human health. Among these microorganisms, phages are the main members of intestinal viromes. In particular, the viral fraction, composed essentially of phages, affects homeostasis by exerting selective pressure on bacterial communities living in the intestinal tract. In recent years, with the widespread use and even abuse of antibacterial drugs, more and more drug-resistant bacteria have been found, and they show a trend of high drug resistance and multidrug resistance. Therefore, it has also become increasingly difficult to treat serious bacterial infections. Phages, a natural antibacterial agent with strong specificity and rapid proliferation, have come back to the field of vision of clinicians and scholars. In this study, the current state of research on intestinal phages was discussed, with an exploration of the impact of phage therapy against infectious diseases, as well as potential application beyond infectious diseases.